2018
DOI: 10.1371/journal.pone.0198808
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating treatments with topical anaesthetic and buccal meloxicam for pain and inflammation caused by amputation dehorning of calves

Abstract: To assess the effects of a topical anaesthetic (TA) and buccal meloxicam (BM) on behaviour, maximum wound temperature and wound morphology following amputation dehorning of beef calves, 50 unweaned Hereford calves were randomly allocated to: (1) sham dehorning / control (CON, n = 14); (2) amputation dehorning (D, n = 12); (3) amputation dehorning with pre-operative buccal meloxicam (DBM, n = 12); and (4) amputation dehorning with post-operative topical anaesthetic (DTA, n = 12). Videos of the calves were captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
(39 reference statements)
1
16
0
Order By: Relevance
“…Widespread adoption by farmers of the addition of an oral NSAID to the procedure currently remains uncertain. However, the use of topical anaesthetic formulation accompanied by intramuscular injections of NSAIDs, administered by beef farmers under veterinary advice, does appear to be increasing in Australia, particularly with recent research confirming both efficacy and productivity improvements with this multimodal approach for use in beef cattle husbandry procedures …”
Section: Resultsmentioning
confidence: 99%
“…Widespread adoption by farmers of the addition of an oral NSAID to the procedure currently remains uncertain. However, the use of topical anaesthetic formulation accompanied by intramuscular injections of NSAIDs, administered by beef farmers under veterinary advice, does appear to be increasing in Australia, particularly with recent research confirming both efficacy and productivity improvements with this multimodal approach for use in beef cattle husbandry procedures …”
Section: Resultsmentioning
confidence: 99%
“…Very little consistent effect of treatment was found on most of the measured behaviours or weight gain over the first 6 days after castration and dehorning (Van der Saag et al 2018b). In a similar study using 6-8 month-old Hereford calves undergoing amputation dehorning alone, there was no clear effect of topical anaesthetic or buccal meloxicam on behaviour, maximum wound temperature or wound morphology after dehorning (Van der Saag et al 2018a). These studies have limited relevance outside Australia and similar extensive range farming systems, as they did not investigate the use of topical anaesthetic alongside local anaesthesia.…”
Section: Introductionmentioning
confidence: 88%
“…Recent research has found that meloxicam-treated, dehorned, 6-to 12-week-old Holstein calves displayed less ear icking for 44 hr and head shaking for 9 hr after dehorning than calves not treated with meloxicam 32 ; moreover, meloxicam signi cantly increased the time spent eating following castration and/or dehorning in 3-month-old Holstein calves 29 . In another study, meloxicam signi cantly reduced the head turning frequency and increased weight gain following castration and dehorning in 6-to 8-month-old beef calves 37 , although clear observations of the effects of meloxicam on other behaviors displayed by 6-to 8-mo-old dehorned beef calves have not been reported 9 . Overall, the changes in behavior suggested that meloxicam was effective in reducing post-surgical pain and distress associated with calf dehorning.…”
Section: Discussionmentioning
confidence: 95%